Nurses in the provision of outpatient care for women with malignant fungating wounds in the breasts - Flávia Firmino; Laísa Figueiredo Ferreira Lós Alcântara (Rev Rene)
This study aimed to analyze accounts of nurses who undertake the dressing of fungating wounds of women with breast cancer, and to outline contributions to the nursing care. This is qualitative research, carried out in November 2010 with interviews and thematic analysis involving five nurses from the outpatient department of a public hospital in the city of Rio de Janeiro, specializing in the treatment of breast cancer. Categories were elaborated corresponding to the practice of outpatient nursing; the cancer wound; and, indications for the nursing care. It is concluded that there is a need for specific knowledge in the area of oncology nursing, professional involvement, technical skill and autonomy, the forming of a therapeutic group, clinical attendance interfacing with the palliative approach, and collaborative work as a team.